Pengaruh Keinginan Pasangan Usia Subur (Pus) dalam Penggunaan Metode Kontrasepsi Jangka Panjang - Sumartini Sumartini; Diah Indriani (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2016)
One of the most eff ective eff ort in the family planning program was to control fertilitas and press the population growth rate was used contraception. In the area of Puskesmas Pacar Keling Surabaya interest of acceptor which used short term contraceptive method still high than long term contraceptive method. This research used analytical observational study with case control methods. The population is all woman reproductive age couples aged 15-49 years old in the area of Puskesmas Pacar Keling Surabaya. Sampling technique used two stage random sampling and got 90 respondent. The variables were age, knowledge, side eff ects, desire to have a child again, husband and family support. Data were analyzed with multiple logistic regression with al level of signifi cance value α= 0,05. The result of logistic regression analysis signifi cant variables were age (p= 0,002), side eff ects (p= 0,005), desire to have a child again (p= 0,028), husband and family support (p= 0,008). Conclusion of research is that age, side effects, desire to have more children, husband and family support infl uencing reproductive age couples using long term contraceptive methods. This research suggest health workers provide Counselling and information about Family Planning to reproductive age couples specially they were 20-30 years old about explanation of the use of long term contraception method.